Mitral valve therapy still surgical?. (9th March 2015) - Fattouch, Khalil; Castriota, Fausto; Guccione, Francesco; Dioguardi, Pietro; Vadalà, Giuseppe; Squeri, Angelo; Russo, Paolo; Cristina Barattoni, Maria; Nasso, Giuseppe; Speziale, Giuseppe
Abstract: Mitral regurgitation (MR) is the second most common valvular heart disease after aortic valve stenosis. With increased understanding of the heterogenic pathophysiology of MR, cardiac surgeons have developed various techniques that increase the likelihood of successful mitral valve repair (MVR). Nowadays, a rate of repair >90% may be reached in some mitral valve reference centres. In recent years, the introduction of transcatheter mitral valve intervention techniques has opened up new frontiers in mitral therapy, specifically in patients at high risk for standard surgery. Current percutaneous technologies for MVR have been developed on the basis of some of the surgical principles. Based on current evidence, surgery remains the standard treatment for MR according to very long-term survival and durability of MVR using Carpentier's technique. Today, in clinical practice, only the MitraClip device may be considered as a real and effective alternative in selected patients with high or prohibitive risk for surgery.